Cross-sectional views of hemoglobin S fibers by electron microscopy and computer modeling. - Garrell, R L (1979)
Fibers of deoxyHb S have been investigated by thin-section electron microscopy, utilizing a tannic acid embedding procedure. On the basis of numerous measurements of cross-sectional center-to-center distances for adjacent fibers in pairs or arrays, fiber diameters (mean +/- SD) of 205 +/- 5 A in embedded cells and 212 +/- 8 A in embedded hemolysates were obtained. This is an agreement with values obtained by conventional embedding procedures [Crepeau, R. H., Dykes, G., Garrell, R. L. & Edelstein, S. J. (1978) Nature (London) 274, 616--617]. The use of tannic acid has resulted in improved resolution of fiber cross sections, revealing individual strands of Hb S molecules. Because the section thickness corresponds to approximately one-fifth of the fiber helical repeat distance, the strands in projection superimpose to form characteristic image patterns. Additional superposition patterns arise in sections taken at small deviations from perpendicularity to the longitudinal fiber axis. These patterns are consistent with the 14-strand structure for hemoglobin S fibers [Dykes, G., Crepeau, R. H. & Edelstein, S. J. (1978) Nature (London) 272, 506--510], as indicated by computer models of cross-sectional patterns for various thicknesses and angular deviations of sections.